Evaluation of tracking devices in a hospital environment - Cho, Jacqueline Hui Ming (2009)
There arc three major paths of spreading infectious diseases. The infectious diseases can spread through physical contact, air-home or spread through vectors (eg. mosquitoes, fleas, lice or ticks) and vehicles (eg. food and water). A pat lent who was admitted to hospital may acquire an infection due to this through any of these three paths. This type of infection is called nosocomial infection. Art individual-based epidemiological simulation model named ASINE (Agent-based Simulation for Infections in the Nosocomial Environment) has been developed in NTU for the purpose of accurately simulating the dynamics of infectious diseases spread among patients and staffs within Tan Tock Seng Hospital (TTSH). Contact tracing is a key element in ASINE. This project focused on the exploration of RFID technology applied as an effective and non- intrusive contact tracing tool to automatic capture data relating to the patients’, health professionals’ and visitors’ activity patterns in a hospital context. The literature study of RFID systems architecture - RFID tags, RFID readers, RFID controllers, host and middleware, communication infrastructures like Bluetooth, Wi-Fi and ZigBee arc covered in this dissertation. This report is centered on the evaluation of two solutions using CADl Scientific he Ltd’s SmartTAG, SmartNODE and SmartSense. They are used for the purpose of contact tracing purpose for ASINE input data collections. The findings and concerns for each solution are individually discussed in the report. Finally, a new solution is proposed to suit the ASINE Movement Profiling usage. Recommendation for future works is also suggested at the end of the report.